Case Report: Acute superior mesenteric artery embolism combined with abdominal aortic aneurysm in an elderly female patient - Wu, Ruixin; Huang, Guofei; Zhou, Yang; He, Junwen; Li, Peiming (Frontiers in Surgery, 2025)
BackgroundBoth acute superior mesenteric artery embolism (ASMAE) and abdominal aortic aneurysm (AAA) are insidious conditions that can lead to fatal outcomes. The coexistence of ASMAE and AAA in a single patient is rare.Methods and resultsA 78-year-old female patient presented to our hospital due to abdominal pain for 10 h, with a diagnosis of AAA 2 h prior. Further evaluation through abdominal aorta computed tomography angiography (CTA) revealed the presence of both ASMAE and AAA. After a comprehensive assessment of her condition, treatment for ASMAE was prioritized. Digital subtraction angiography of the abdominal aorta and superior mesenteric artery (SMA) was performed, followed by local thrombolysis of the SMA embolism and two sessions of AngioJet mechanical thrombectomy. Once inflammation parameters have normalized and an active infection could be excluded, the patient subsequently underwent endovascular aneurysm repair (EVAR) for the AAA. Regular follow-up CTA over three years demonstrated that the SMA remained patent, and the abdominal aortic covered stent was intact, there were no significant endoleaks or thrombosis, with no evidence of stenosis in the abdominal aorta.ConclusionThe simultaneous occurrence of ASMAE and AAA is uncommon. ASMAE poses a significant threat to life and necessitates urgent treatment. Unruptured AAA can be treated electively once any contraindications have been addressed.